Study on the Photodegradation Stability of Poly(butylene Succinate-co-butylene Adipate)/TiO2 Nanocomposites - Lihai Cai; Zhiguo Qi; Jun Xu; Baohua Guo; Zhongyao Huang (Journal of Chemistry)
A poly(butylene succinate-co-butylene adipate)/TiO2 (PBSA/TiO2) nanocomposite was prepared by a melt-blending process. The effect of TiO2 nanoparticles on the photodegradation behaviors of the nanocomposite was investigated by transmission electron microscopy (TEM), differential scanning calorimetry (DSC), Fourier-transform infrared spectroscopy (FT-IR), field-emission scanning electron microscopy (FE-SEM), rheological measurements, and mechanical tests. TEM images of the PBSA/TiO2 revealed that the TiO2 nanoparticles were well dispersed in the matrix without obvious aggregation. The FT-IR results indicated that the TiO2 nanoparticles can block high-energy ultraviolet (UV) light and reduce the degradation of the PBSA matrix. The viscosity analysis results indicated that the TiO2 nanoparticles inhibited the chain scission of PBSA matrix under irradiation. In addition, the surface of the PBSA/TiO2 films and their mechanical properties change less than that of untreated PBSA films during the photoaging process. The obtained results imply that the TiO2 nanoparticles can be considered as an efficient photodegradation-resistant additive to PBSA for reducing photodegradation.